Vanilla pompona Leaves and Stems as New Sources of Bioactive Compounds: The Therapeutic Potential for Skin Senescence - Wang, Duanyang; Amen, Yhiya; Elsbaey, Marwa; Nagata, Maki; Matsumoto, Masako; Wang, Dongmei; Shimizu, Kuniyoshi (Planta Medica, 2023)
A large variety of natural plants are widely produced and utilised because of their remarkable pharmacological effects. In this study, two phenolic glycosides were isolated for the first time from Vanilla pompona Schiede (Orchidaceae) from Kyushu, Japan: bis [4-(β-D – O-glucopyranosyloxy)-benzyl] (S)-2-isopropylmalate (1) and bis 4-[β-D-O-glucopyranosyloxy)-benzyl]-(2R,3S)-2-isopropyl tartrate (2). We have discovered that the crude extract of V. pompona leaves and stems and its two phenolic glycosides (compounds 1 – 2) are highly effective in reversing skin senescence. V. pompona and compounds 1 – 2 were found to promote the synthesis of collagen, hyaluronic acid, and elastin in skin fibroblasts in a normal skin cell model; in a replicative senescence model, V. pompona and compounds 1 – 2 significantly reduced the ageing phenotype in skin fibroblasts. These compounds also demonstrated a significant protective effect in a UV-induced photo-senescence model; the possible mechanisms of this effect were investigated in this study. To the best of our knowledge, this study is the first to develop V. pompona leaves and stems as new sources of bioactive compounds and to examine their therapeutic potential for skin senescence. The development potential of V. pompona leaves and stems for use in the cosmetics, cosmeceutical, and pharmaceutical industries remains to be investigated.
Keywords: Vanilla pompona; Orchidaceae; Vanilloideae; bioactive compounds; cosmeceutical; senescence; skin fibroblasts